General Synthesis of N‐Doped Macroporous Graphene‐Encapsulated Mesoporous Metal Oxides and Their Application as New Anode Materials for Sodium‐Ion Hybrid Supercapacitors. (25th November 2016) - Kim, Min Su; Lim, Eunho; Kim, Seongbeen; Jo, Changshin; Chun, Jinyoung; Lee, Jinwoo
Abstract : A general method to synthesize mesoporous metal oxide@N‐doped macroporous graphene composite by heat‐treatment of electrostatically co‐assembled amine‐functionalized mesoporous silica/metal oxide composite and graphene oxide, and subsequent silica removal to produce mesoporous metal oxide and N‐doped macroporous graphene simultaneously is reported. Four mesoporous metal oxides (WO3− x, Co3 O4, Mn2 O3, and Fe3 O4 ) are encapsulated in N‐doped macroporous graphene. Used as an anode material for sodium‐ion hybrid supercapacitors (Na‐HSCs), mesoporous reduced tungsten oxide@N‐doped macroporous graphene (m‐WO3− x @NM‐rGO) gives outstanding rate capability and stable cycle life. Ex situ analyses suggest that the electrochemical reaction mechanism of m‐WO3− x @NM‐rGO is based on Na + intercalation/de‐intercalation. To the best of knowledge, this is the first report on Na + intercalation/de‐intercalation properties of WO3− x and its application to Na‐HSCs. Abstract : N‐doped macroporous graphene‐encapsulated mesoporous metal oxides for new energy storage systems, namely, sodium‐ion hybrid supercapacitors (Na‐HSCs), are presented. An Na‐HSC system comprising an N‐doped macroporous graphene‐encapsulated mesoporous tungsten oxide anode and an MSP‐20 cathode delivers high energy and power densities, with excellent cycling stability.